2014
DOI: 10.1136/bmjopen-2014-005694
|View full text |Cite
|
Sign up to set email alerts
|

HCV seropositivity in inmates and in the general population: an averaging approach to establish priority prevention interventions

Abstract: ObjectivesDespite the fact that a considerable portion of hepatitis C virus (HCV) positive individuals are viraemic, the risk of transmitting HCV to others is context dependent. Prison is a particularly risky environment as HCV prevention tools are often unavailable. Using data from a cross-sectional study conducted in centres for HCV testing in southeastern France, we aimed to compare the patterns of risk factors in HCV-positive inmates with those in the general population.Setting26 centres for HIV/HCV testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
2
10
2
1
Order By: Relevance
“…Infected blood can be recovered from snorting straws, and sharing these is common . Cohort studies of HCV‐infected non‐injecting cocaine users , men who have sex with men and prison inmates have found snorting to be a risk factor for HCV exposure, but others have not . Our finding of low HCV prevalence in people not on OST/injecting use does not support sharing snorting straws as a major risk for HCV transmission.…”
Section: Discussioncontrasting
confidence: 59%
“…Infected blood can be recovered from snorting straws, and sharing these is common . Cohort studies of HCV‐infected non‐injecting cocaine users , men who have sex with men and prison inmates have found snorting to be a risk factor for HCV exposure, but others have not . Our finding of low HCV prevalence in people not on OST/injecting use does not support sharing snorting straws as a major risk for HCV transmission.…”
Section: Discussioncontrasting
confidence: 59%
“…Mohamed et al, 2013 (10) documented that the best predictor for hepatitis C and hepatitis B infections were intravenous drug use, longer duration spent in prison (>10 years) and shared toiletries. Different results were found by Roux et al, 2014 (16) whose study revealed that drug injection without snorting' and 'drug injection with snorting' were very strongly associated with HCV seropositivity. Among inmates, 'drug snorting alone' (OR (95% CI) 2.21 (1.39 to 3.52) was also a strong correlate while tattoos, piercings (OR (95% CI) 1.22 (0.92 to 1.61)) and the sharing of toiletry items (OR (95% CI) 1.44 (0.84 to 2.47)) were weak correlates.…”
Section: Discussionmentioning
confidence: 67%
“…Adjei et al, 2006 (15) revealed similar seroprevalence of HCV (19.0%) while the HBsAg recorded 17.4% in prisons in Ghana, the difference in the prevalence of HBV may be attributed to the difference in the marker used for diagnosis. In France, Roux et al, 2014 (16) reported a significantly higher prevalence of HCV in inmates (5%) than in general population (2%).…”
Section: Discussionmentioning
confidence: 99%
“…Although imprisonment puts people at a high risk of HCV infection, this is through risky behaviors that take place before or during imprisonment such as injecting drug use. While injecting drug use is likely to be the most common HCV transmission pathway among prison inmates, it is not the only one (161). This complex situation may be difficult to tease apart with existing evidence.…”
Section: Discussionmentioning
confidence: 99%